Dielectric characterization of NixCo1-xFe2O4 nanocrystals thin film over a broad frequency range (1 MHz-3 GHz) - ESMER, KADİR (AMER INST PHYSICS, 2010)
We have theoretically and experimentally investigated the dielectric behavior of NixCo1-xFe2O4 nanoparticles (NPs) (where x=0.0, 0.6, and 1.0), which have been synthesized by microwave induced combustion synthesis using urea as fuel. A variation of complex dielectric permittivity at room temperature with frequency in the range 1 MHz-3 GHz has been studied. The permittivity displays atomic polarization and electronic polarization. Particles showed phase purity and crystallinity in powder x-ray diffraction (XRD) analysis. At the same time, NixCo1-xFe2O4 NPs demonstrated a spinel cubic structure from XRD results.
Keywords: cobalt compounds; combustion synthesis; crystal structure; crystallisation; dielectric polarisation; dielectric thin films; ferrites; nanoparticles; nickel compounds; permittivity; X-ray diffraction; MAGNETIC CHARACTERIZATION; COMBUSTION SYNTHESIS; FERRITE; COBALT; COFE2O4; CO; NANOPARTICLES; PERMITTIVITY; PERMEABILITY; NICKEL